2008
DOI: 10.1111/j.1548-1387.2008.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Before Your Very Eyes: Illness, Agency, and the Management of Tourette Syndrome

Abstract: In this article, I examine the ways that people with Tourette Syndrome (TS) manage the motor and vocal tics characteristic of this neurological disorder. To mitigate the powerful stigmas associated with TS, individuals must either remove tics from public view or strive to recast the way that they are perceived. Drawing on ethnographic research with TS sufferers in Indiana, I elaborate three strategies by which this is done, strategies referred to here as displacement, misattribution, and contextualization. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…This avoided aversive stigmatization such as bullying, and instead facilitated the opportunity for social acceptance and integration. However, the literature suggests that such strategies could further maintain social/cultural stigma or confusion about control, illness, and society's understanding of TS (Buckser, ). Despite the use of such strategies, individuals expressed concern for their future.…”
Section: Resultsmentioning
confidence: 99%
“…This avoided aversive stigmatization such as bullying, and instead facilitated the opportunity for social acceptance and integration. However, the literature suggests that such strategies could further maintain social/cultural stigma or confusion about control, illness, and society's understanding of TS (Buckser, ). Despite the use of such strategies, individuals expressed concern for their future.…”
Section: Resultsmentioning
confidence: 99%
“…Only 17 of these reported data from independent projects as two sets of articles discussed data from the same study [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] (Fig. 1).…”
Section: Included Studiesmentioning
confidence: 93%
“…Nevertheless, by studying the articles providing narratives of individuals with TS, the concept of stigma or the components of it emerge [41][42][43][44][45][46][47][48]. It should be noted, however, that the perceived public stigma in the reports of individuals with TS may also reflect and be influenced by self-stigma depression, anxiety [5] or anticipated rejection [57].…”
Section: Qualitative Studiesmentioning
confidence: 97%
“…O'Connor's study however, examines representations of illness on groups of individuals with various conditions rather than focussing on TS and therefore fails to delve into the specific experiences of adults with TS. Buckser's (2008) ethnographic study indicated that the suppression and concealment of tics by people with TS appeared to be a mechanism to resist the undesirable disability labeladults with TS wishing to dissociate themselves from 'disabled' groups. Yet, self-concept and social identity were not discussed in Buckser's study and there is a gap in the literature that provides a broader understanding of the individuals' lived experience.…”
Section: Introductionmentioning
confidence: 99%